Production of Biodiesel Using Enzymatic Esterification of Multi-Feedstock Oils - Indro Sumatri; H. Hadiyanto; S. Suherman; Marcelinus Christwardana (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
Biodiesel is produced from oils esterified with alcohol into glycerol and water. Vegetable edible oil raw materials are the main consideration in biodiesel production. This study used three types of oil, namely palm oil (PO), waste frying oil (WFO), soybean oil (SO), and corn oil (CO), with the catalyst of the enzyme lipase. The price of WFO as raw materials is low, although it must be controlled acid and water levels. In the research run, the oil mixture consists of two types of oils mixed with a certain composition and the addition of certain lipase enzymes. The research resulted that the yield produced by multi-feedstock biodiesel with free fatty acid (FFA) < 2 was 89.7%, 89.03%, and 86.11% higher than the sample with FFA > 2 at 79.54%, 74.66%, and 73.33%, respectively. The minimum density produced is a mixture of WFO with CO of 861.1 kg/m3. The largest viscosity produced is a mixture of WFO with SO of 18.03 mm2/s. Mixing raw materials can lower the number of iodine multi-feedstock biodiesel. The number of acids produced by multi-feedstock biodiesel exceeds ASTM standards. The total glycerol produced by multi-feedstock biodiesel varies, whereby a multi-feedstock blend of PO can lower total glycerol. In contrast, a multi-feedstock blend of WFO tends to produce high total glycerol.